הדיבור העברי: קריא מחודשת - Ginsburg, Shai; Barzilai, Maya (מכאן, 2020)
In most histories of Modern Hebrew, scholars locate the emergence of the spoken language in Ottoman Palestine at the turn of the 20th century. This article traces, by contrast, how Hebrew was predominantly spoken outside of Palestine, accompanying the development of Modern Hebrew writing in the Russian Pale of Settlement, Austrian Galicia, the Ottoman Balkan, and the United States. The spread of Modern Hebrew speech outside of Palestine can be attributed to the Heder metukan, a reformed school for Jewish children, instituted in the Pale of Settlement in the early 1890s. Tens of thousands of children were educated in such Hadarim worldwide up until the outbreak of World War I. We maintain that renewed attention to the predominance of spoken Hebrew in Eastern Europe can change our understanding of Hebrew lterary critism, literary historiography and Hebrew itself. In the case of Galician poet Avraham Ben Yizhak, we show that the Heder metukan and its pedagogy thoroughly informed his approach to Hebrew poetry in the early 20th century. We read his minimalist modernism as also being informed by the direct and concrete approach to Hebrew acquisition practiced by teachers who teach Hebrew in Hebrew.